Characteristics of Bread and Biscuit Made With Wheat and Rice Flour Composites - Hrušková, Ivan Švec Marie (Journal of Food Technology Research, 2014)
Technological quality changes of wheat flour were studied in relation to its partial replacement (5, 10, 15, 20, 25 or 30%) by white rice flour (RF). In dependence on level added, RF lowered water absorption up to about 10%. Dough stability was multiplied reversely as well as its overmixing tolerance – softening degree of dough lessened from 60 Brabender units (BU) for wheat flour to 20 BU for wheat-rice flour blend 70:30. Baking quality of flour composites was worsened owing to changes in dough elasticity and extensibility (i.e. dough machinability), summarised by extensigraph energy (as an area under curve) decrease from 140 cm2 to 70 cm2 comparing the same samples. Gelatinisation temperatures and amylograph maxima reversely increased – optimal values were recorded for wheat:rice composite 80:20 yet (viscosity between 575 – 790 BU). Fermentation process was affected equivocally – gases volumes had increased up to about 11% because of glucosidase present in RF, but dough volumes lowered due to gluten net weakening. It resulted into lowering of control bread volume to a half for the bread containing 30% of RF (from 319 to 154 ml/100 g, respectively). Bread crumb chewiness was affected seriously; bread samples higher level of RF than 20% were less acceptable (fall of crumb penetration from 10.6 mm to 2.2 mm). Quality changes of biscuits containing RF were of smaller extent – the substitution of 5% caused specific volume increase about ca 15% (from 143 to 203 ml/100 g). Sizes of other fortified biscuits were gradually diminished to level of the wheat control ones.